Restriction of orientation variability and spatial frequency on the perception of average orientation. (July 2022) - Takebayashi, Hikari; Saiki, Jun
During the observation of a single object, orientation and spatial frequency are jointly coded in an early stage of visual processing, as is evident from studies on the aftereffects of specific combinations of both these features. However, they become independent in the decision-making stage because observers can identify one feature while ignoring the other. Does this separability expand into the perception of ensemble representations? This study investigated the effect of the spatial frequencies of Gabor patches on orientation averaging. In the experiment, the average orientations of all eight patches composed of either homogeneous (i.e., eight 3 cycles/degree or 0.8 cycles/degree patches) or heterogeneous (i.e., four 3 cycles/degree and four 0.8 cycles/degree patches) spatial frequencies were stably estimated if the orientation varied within the range of ±7.7° around the true mean. However, when the range was extended to ±14°, we found that the averaging performance was better in the homogeneous lower spatial frequency than in the homogeneous higher spatial frequency and heterogeneous spatial frequency conditions. These results suggest that an ensemble perception of orientation is modulated by spatial frequency components.